Peran Penyuluh Agama Islam dalam Memberikan Motivasi Terhadap Warga Binaan Panti Sosial Di Kabupaten Malang - Putri, Sherla Amanda; Subhi, Muhamad Rifa'i (Jurnal Penyuluhan Agama, 2024)
Abstract: Social institutions are institutions that empower people with social welfare problems (PMKS), including homeless people and individuals with mental problems. The social and psychological challenges faced by inmates, such as social isolation and uncertainty about the future, emphasize the urgency of providing motivation as a source of inspiration and emotional support. The role of Islamic religious extension is key in providing inspiration, emotional support, and stimulating positive change. Through counseling and guidance, religious extension help inmates find the meaning of life, reflect on their actions, and create positive change. The aims of this research are 1) to find out the role of religious Islamic extension as motivators for assisted residents in social institutions, 2) to determine the positive impact of providing motivation to social assistance residents in social institutions. This research uses a qualitative approach using the literature study method which was carried out at the beginning of the research concept formulation stage. The results of this research show that 1) the role of religious extension as motivators proves the importance of their contribution in guiding, inspiring, and building the psychological and moral well-being of social assistance residents (WBS), 2) the positive impact of providing motivation on social assistance residents, shows that religious extension has a significant role in forming positive character and improving the mental well-being of social assistance members (WBS).ositive character and improving the mental well-being of social assistance members (WBS). Abstrak: Panti sosial adalah lembaga yang memberdayakan Penyandang Masalah Kesejahteraan Sosial (PMKS), termasuk tunawisma dan individu dengan masalah kejiwaan. Tantangan sosial dan psikologis yang dihadapi warga binaan, seperti isolasi sosial dan ketidakpastian masa depan, menekankan urgensi memberikan motivasi sebagai sumber inspirasi dan dukungan emosional. Peran penyuluh agama Islam menjadi kunci dalam memberikan inspirasi, dukungan emosional, dan merangsang perubahan positif. Melalui konseling dan bimbingan, penyuluh agama membantu warga binaan menemukan makna hidup, merenungkan tindakan mereka, dan menciptakan perubahan positif. Tujuan penelitian ini adalah 1) mengetahui bagaimana peran Penyuluh Agama Islam sebagai motivator warga binaan di Panti Sosial, 2) mengetahui dampak positif pemberian motivasi pada warga binaan sosial di Panti Sosial. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode studi pustaka yang dilakukan pada awal tahap perumusan konsep penelitian. Hasil dari penelitian ini menunjukkan bahwa 1) peran penyuluh agama sebagai motivator membuktikan pentingnya kontribusi mereka dalam membimbing, memberikan inspirasi, dan membangun kesejahteraan psikologis serta moral warga binaan sosial (WBS), 2) dampak positif pemberian motivasi pada warga binaan sosial, menunjukkan bahwa penyuluh agama memiliki peran signifikan dalam membentuk karakter positif dan meningkatkan kesejahteraan mental warga binaan sosial (WBS).